(untitled) (Journal of the College of Basic Education, 2022)
Fantasy has been associated with one of the important film genres, which is (science fiction films), so any talk about fantasy is unintentionally linked to these films, so the concept of fantasy becomes mixed with the concept of science fiction in cinema.And because the imagination in the art of cinema is not linked to science fiction films specifically, as the essence of pleasure in any film does not come from a mere idea or story, but rather from the imagination of the artist, which prevents him from completely submitting to reality. Therefore, it is necessary to stand on this fact. Hence, the research problem was manifested in answering the following questions:1- What are the levels of imagination in the film? What are its aesthetic capabilities?2- Are all types of films built through a model of vision that relies on imagination?